Economic Crises and Emission of Pollutants: a Historical Review of Select Economies amid Two Economic Recessions - Stavytskyy, Andriy; Giedraitis, Vincent; Sakalauskas, Darius; Huettinger, Maik (Ekonomika, 2016)
This paper investigates the historical trends in economic development through the impact of economic depressions and emissions of greenhouse gasses, namely carbon dioxide (CO2). The analysis includes four countries: the United States, the United Kingdom, Germany and Japan. The focus, therefore, will be on the impact of two economic crises and their effect on global warming. Temperature changes in the longer period are very often regarded as a result of human activity, which can be measured by the increase of GDP (per capita). The findings indicate that GDP (per capita) parameters cannot be considered as correct measures of human pollution activity. The results show that the long-run temperature can be evaluated with the help of annual average temperatures of the previous four years. The proposed model does not only provide quite satisfactory forecasts, but is very stable with coefficients variables that can make a model more reliable for practice.
Keywords: economic influence; climate changes; global warming; Schumpeter; time series; forecasting